Nanostructured lipid carrier containing hydroxymethylnitrofurazone: preparation, characterization and in vitro and in vivo evaluation of leishmanicidal activity - Souza, Aline de (2021)
Leishmaniasis, a neglected tropical disease (NTD), is a set of diseases caused by obligatory parasitic protozoa of the genus Leishmania. And it has cutaneous and visceral eishmaniasis as its main forms. Treatment includes pentavalent antimonials. These drugs have several disadvantages, such as the need for parenteral administration, use of high dosages, long duration of treatment, severe toxicity, resistance and variable efficacy. The candidate for hydroxymethylnitrofural drug (NFOH), a prodrug derived from nitrofural, showed high activity in cell cultures infected with Trypanosoma cruzi and less toxicity when compared to nitrofural. Due to its low solubility in water and reduced bioavailability, NFOH has failed the in vivo efficacy tests. Nanostructured drug delivery systems have the potential to overcome these challenges due to their evident advantages: greater therapeutic efficacy, less toxicity, modified drug release and increased gastrointestinal absorption of drugs with low water solubility. The objective of this project will be the preparation and evaluation of the physicochemical characteristics of a nanostructured lipid carrier containing hydroxymethylnitrofural (NLC-NFOH). The NFOH showed the highest solubility in Miglyol® 840 among the tested liquid lipids. For solid lipids, Gelucire® 50/13 and Precirol® ATO5 proved to be more suitable for the solubilization of NFOH. The optimized NLC-NFOH consisted of these three lipids. These lipids were selected using a quick Technobis Crystal 16TM methodology, microscopy and DSC. Different lipid selection tools provided scientific knowledge relevant to the development of NLC. The NLC-NFOH had an average z of 198.6 ± 5.4 nm, a PDI of 0.11 ± 0.01 and a zeta potential of -13.7 ± 0.7 mV. This study allowed a design space development approach of the first NLC-NFOH with the potential to treat leishmaniasis orally. The development of a sensitive bioanalytical method using HPLC and evaluation of some analytical figures of merit for the validation allowed the quantification of NFOH and NF. The bioanalytical method for analysis of NFOH and NF use Zorbax SB-C18, 5µm, (4.6x250mm) HPLC column. The mobile phase was consisted of acetonitrile:water (20:80 v/v) with flow rate of 1.2 ml/min, at UV detection of 370 nm. The linearity of NFOH and NF was found in the range 0.0253.0 µg/ml with a correlation coefficient of r > 0.98. The precision was 2.44 to 13.77% for NFOH and 2.61 to 18.42%; the accuracy was 2.66 to 14.28% for NFOH and 2.09 to 19.06% for NF. The method showed to be suitable for effectively evaluation of NFOH is serum. NLC-NFOH (2.8 mg/kg) was administered to animals by gavage, and the blocking flow of the chylomicrons model was performed with an intraperitoneal injection of cycloheximide. The presence of NFOH in serum was evaluated with and without cycloheximide. The cytotoxicity assay of NLC-NFOH and blank-NLC showed more than 90% viable cells at the maximum concentration used (2560 µM). NFOH and NF were detected at 1h after the gavage of DMSO-NFOH or NLC-NFOH, without the pretreatment with cycloheximide. The concentration found for DMSO-NFOH and NLC-NFOH were 0.0316 and 0.0291 µg/mL, respectively. The NLC presented the NFOH absorption by the lymphatic system, demonstrated by blocking chylomicrons flow.